How Do I Lower Pressure in My Distribution System?. Issue 5 (1st May 2016) - Gimson, Mark; Duque, Alejandro
Abstract : If pressure fed into a zone needs to be lowered, traditionally the method used is to install a pressure‐reducing valve (PRV). Such a valve will limit a valve's outlet pressure to a preset pressure regardless of the flow rate and the inlet pressure.